Proteomic Identification of Betaig-h3 as a Lysophosphatidic Acid-Induced Secreted Protein of Human Mesenchymal Stem Cells: Paracrine Activation of A549 Lung Adenocarcinoma Cells by Betaig-h3 - Shin, Sang Hun (The American Society for Biochemistry and Molecular Biology, 2012)
Lysophosphatidic acid (LPA) is enriched in the serum and malignant effusion of cancer patients and plays a key role in tumorigenesis and metastasis. LPA-activated mesenchymal stem cells promote tumorigenic potentials of cancer cells through a paracrine mechanism. LPA-conditioned medium (LPA CM) from human adipose tissue-derived mesenchymal stem cells (hASCs) elicited adhesion and proliferation of A549 human lung adenocarcinoma cells. To identify proteins involved in the LPA-stimulated paracrine functions of hASCs, we analyzed the LPA CM using liquid-chromatography tandem mass spectrometry-based shotgun proteomics. We identified βig-h3, an extracellular matrix protein that is implicated in tumorigenesis and metastasis, as an LPA-induced secreted protein in hASCs. LPA-induced βig-h3 expression was abrogated by pretreating hASCs with the LPA receptor(1/3) inhibitor Ki16425 or small interfering RNA-mediated silencing of endogenous LPA(1). LPA-induced βig-h3 expression was blocked by treating the cells with the Rho kinase inhibitor Y27632, implying that LPA-induced βig-h3 expression is mediated by the LPA(1)– Rho kinase pathway. Immunodepletion or siRNA-mediated silencing of βig-h3 abrogated LPA CM-stimulated adhesion and proliferation of A549 cells, whereas retroviral overexpression of βig-h3 in hASCs potentiated it. Furthermore, recombinant βig-h3 protein stimulated the proliferation and adhesion of A549 human lung adenocarcinoma cells. These results suggest that hASC-derived βig-h3 plays a key role in tumorigenesis by stimulating the adhesion and proliferation of cancer cells and it can be applicable as a biomarker and therapeutic target for lung cancer.